An Eye on Vision: Seven Questions About Vision Screening and Eye Health—Part 4. (November 2018) - Nottingham Chaplin, P. Kay; Baldonado, Kira; Cotter, Susan; Moore, Bruce; Bradford, Geoffrey E.
Current evidence-based and best-practice vision screening and eye health approaches, tools, and procedures are the result of revised national guidelines in the past 3 years and advances in research during the past 18 years. To help the busy school nurse with little time to keep up with changes in children's vision practices and a growing body of literature, the National Center for Children's Vision and Eye Health at Prevent Blindness is providing answers to seven questions that are often received from the field. Topical areas are (1) instrument-based screening and stereopsis, (2) optotype-based screening if child is referred from instrument-based screening, (3) next steps if a student's glasses are scratched or broken, (4) critical line screening with a threshold eye chart, (5) full threshold screening if student does not pass critical line screening, (6) holding a ruler beneath line of optotypes to identify, and (7) convergence insufficiency screening in the school setting.